Young, Empowered and Strong: A Web-Based Education and Supportive Care Intervention for Young Women With Breast Cancer Across the Care Continuum. (2021) - Sella, Tal; Snow, Craig; Freeman, Hannah; Poorvu, Philip D.; Rosenberg, Shoshana M.; Partridge, Ann H.
Abstract : PURPOSE: Patient-centered digital interventions may help empower young women to self-manage symptoms and psychosocial concerns and support informational needs often unaddressed in clinic. METHODS: Young, Empowered and Strong (YES) is an interactive web-based intervention designed to engage young women with personalized education and symptom self-management resources on the basis of responses to patient-reported outcome–based questionnaires. We piloted YES among young women (< 45 years) with newly diagnosed early breast cancer (EBC) or metastatic breast cancer (MBC) and breast cancer survivors (BCSs). Assessments were deployed weekly (EBC and MBC) or every 4 weeks (BCSs) over 12 weeks. At study completion, use, feasibility, and acceptability of YES were evaluated via a survey and semistructured interview. RESULTS: Thirty women were enrolled between April and June 2019: 10 EBC, 10 BCSs, and 10 MBC. The mean age at diagnosis and enrollment was 36 (range 25-44) and 39 (range 31-44) years, respectively. Most participants were actively treated (96%, 27 of 28) with endocrine therapy (54%, 15 of 28) or chemotherapy (43%, 12 of 28). Overall, 61% (180 of 296) of assessments were completed (EBC: 70%, BCSs: 63%, and MBC: 52%). Of 37 patient-reported outcome and need domains, the most frequently triggered were sexual health (EBC: 90%, BCSs: 90%, and MBC: 90%), anxiety (EBC: 80%, BCSs: 90%, and MBC: 90%), stress and mindfulness (EBC: 80%, BCSs: 90%, and MBC: 90%), and fatigue (EBC: 90%, BCSs: 80%, and MBC: 90%). On postpilot survey, participants reported that YES helped them to learn (50%, 7 of 14), monitor (43%, 6 of 14), and manage (57%, 8 of 14) their symptoms. CONCLUSION: YES is a feasible and acceptable digital intervention to support young women across the breast cancer care continuum. The nearly universal triggering of sexual and mental health needs suggests suboptimal management in the clinical setting and the potential for self-management through a digital platform.